Geospatial database of livestock producers in Colombia - Pérez Bolaños, Juliana (2024)
The GDB collects and analyses geospatial and descriptive data on livestock producers in Caquetá participating in sustainable practices of the Rutas PDET project. It includes information on the location of farms in La Montañita, El Paujil, San Vicente del Caguán and Puerto Rico, areas of implementation of sustainable livestock technologies, and producer profiles. This GDB is essential for project planning and monitoring, facilitating informed decisions, and continuous evaluation. Key concepts: farm location, sustainable livestock technologies, regional sustainability, and conservation. Spanish: La GDB recopila y analiza datos geoespaciales y descriptivos sobre los productores de ganado en Caquetá que participan en prácticas sostenibles del proyecto Rutas PDET. Incluye información sobre la ubicación de los predios en La Montañita, El Paujil, San Vicente del Caguán y Puerto Rico, áreas de implementación de tecnologías ganaderas sostenibles, y perfiles de los productores. Esta GDB es esencial para la planificación y monitoreo del proyecto, facilitando decisiones informadas y evaluación continua. Conceptos clave: localización de predios, tecnologías ganaderas sostenibles, sostenibilidad regional, conservación.